2009
DOI: 10.1002/cjoc.200990112
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Studies on the Binding of Bacteriophage Mequindox with Bovine Serum Albumin

Abstract: Fluorescence spectra and UV-Vis absorption spectra have been used to study the binding of bacteriophage mequindox (MEQ) with bovine serum albumin (BSA), which performed a dynamic quenching process. The quenching constants and thermodynamic parameters at different temperatures were calculated. The binding was primarily driven by entropy, and hydrophobic forces also played a significant role. The distance between BSA and MEQ was estimated to be 4.5 nm based on the theory of Förster's non-radioactive energy trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…The maximum emission wavelengths of tyrosine residues shifted towards short wavelength upon addition of PMT, which indicated that the polarities around tyrosine residues were decreased and the hydrophobicity was increased and the amino acid residues were less exposed to the solvent with the addition of PMT [40]. Three-dimensional fluorescence spectroscopy is a new analytical technique which is applied to investigate the conformational changes of proteins in recent years [41,42]. The excitation wavelength, the emission wavelength and the fluorescence intensity can be used as the axes making the investigation of the characteristic conformational changes of proteins be more scientific and credible [43,44].…”
Section: Conformation Investigationmentioning
confidence: 99%
“…The maximum emission wavelengths of tyrosine residues shifted towards short wavelength upon addition of PMT, which indicated that the polarities around tyrosine residues were decreased and the hydrophobicity was increased and the amino acid residues were less exposed to the solvent with the addition of PMT [40]. Three-dimensional fluorescence spectroscopy is a new analytical technique which is applied to investigate the conformational changes of proteins in recent years [41,42]. The excitation wavelength, the emission wavelength and the fluorescence intensity can be used as the axes making the investigation of the characteristic conformational changes of proteins be more scientific and credible [43,44].…”
Section: Conformation Investigationmentioning
confidence: 99%
“…According to the supplier, the average pore diameter of the γ-Al 2 O 3 is about 0.2 μm. Ultra-thin Pd membranes were deposited on γ-Al 2 O 3 surface by a modified electroless plating method [38]. Four…”
Section: Preparation Of Pd Composite Membranesmentioning
confidence: 99%
“…10,20 Pd and Ag both crystallise in the face-centred cubic (fcc) lattice with lattice constants of 389.07 and 405.83 Ǻ respectively. [20][21][22] The infinite miscibility of the two elements means that the expansion of the Pd lattice as Ag is doped into the structure is linear. [20][21][22] The resistivity and thus electrical conductivity of Pd-Ag alloys, vary extensively with both temperature and composition.…”
Section: Physiochemical and Mechanical Propertiesmentioning
confidence: 99%
“…[20][21][22] The infinite miscibility of the two elements means that the expansion of the Pd lattice as Ag is doped into the structure is linear. [20][21][22] The resistivity and thus electrical conductivity of Pd-Ag alloys, vary extensively with both temperature and composition. 13 The room temperature variation with alloy composition is outlined in Figure 1.…”
Section: Physiochemical and Mechanical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation